Retrospective audit of genital prolapse management - Rohini, E.; Indu, N. R.; Banu, A. Shameera; Hiremath, P. B.; Hiremath, Reshma (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Pelvic organ prolapse is a descent of the pelvic organs into the vagina, frequently associated with local pelvic symptoms. Pelvic floor support is essential to maintain the normal anatomy. Recent studies of genital prolapse suggests that it is more important to improve the patient satisfaction and reduce complication than to achieve anatomical success. The purpose of the audit of genital prolapse management in this retrospective study is to know and understand the decision making, selection of patients for a particular surgery and to know and avoid the complications of genital prolapse management. Methods: This retrospective descriptive study was conducted at SVMCH and RC during the period of January 2020 to December 2021. The detailed analysis of the cases, symptomatology, surgical methods, complications and follow up were studied. Results: We managed 110 cases of genital prolapse. 35 patients had massive/ huge genital prolapse (POP Q Stage 4). 75.4%were found in the age group beyond 55 years, 66.3% were multiparous. 31% of the patients came with massive prolapse (POP Q-stage IV), 5% showed cervical elongation ,7% showed vault prolapse, Majority of our patients (63%) were managed by vaginal hysterectomy with pelvic floor repair. Followed by pessary, Fothergill’s surgery, Purandare’s surgery, Le forte’s, sacrospinal fixation, hysterosacropexy, pessary with thiersch stitch. Conclusions: The choice of management of genital prolapse has to be tailored according to the patients needs and pathology. The younger trainees have to be trained to get the skills of various surgeries of genital prolapse.